Beyond clinical dehumanisation toward the other in community mental health care : levinas, wonder and autoethnography - Racine, Catherine A. (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Beyond Clinical Dehumanisation Toward the Other offers a rare and intimate portrayal of the moral process of a mental health clinician that interrogates the intractable problem of systemic dehumanization in community mental health care, and looks to the notion of 'wonder,' and the visionary relational ethics of Emmanuel Levinas, for a possible cure. This book is an ethical primer for mental health professionals, researchers, educators, advocates and service users working to re-imagine and heal a broken system by challenging the underpinnings of entrenched dehumanization and standing with those they "serve""--
OCLC-licensed vendor bibliographic record.
Keywords: Psychiatric ethics; Community mental health services -- Moral and ethical aspects; PHILOSOPHY / Ethics & Moral Philosophy; PSYCHOLOGY / Clinical Psychology; PSYCHOLOGY / Movements / Psychoanalysis